A Conversation on Building Resilience and Protecting Children: An Evidence-Based Family Strengthening Approach - Mary M. McKay; Mary Acri (Washington University Journal of Law & Policy, 2018)
This Article summarizes a presentation to child mental health scientists, child development experts, neuroscientists, and child health practitioners at a 2017 conference entitled “The Developing Brain: New Directions in Science, Policy, and Law.” We presented an evidence-based approach to strengthening families, referred to as the “4Rs and 2Ss Family Strengthening Program,” as an option for protecting children and enhancing their overall development. We presented data that found child and family outcomes, including child behavior regulation and functioning, and parent depression and stress, improved among families who participated in the intervention. We also found several intervention innovations that were developed as a result of intensive collaboration with adult caregivers, child mental health providers and services researchers. These innovations include: 1) a multiple family group format composed of up to eight families, and in which at least two generations of each family attend the group; 2) family advocates (trained caregivers that have cared for a child with mental health problems) as group co-facilitators; 3) an intervention protocol that is shared with providers and families; and 4) content that increases transparency of the evidence-based principles including establishing family rules, fostering healthy parent/child relationships, enhancing caregiver social support and decreasing stress. Evidence-based interventions that support parenting and family processes offer opportunities to meet challenges threatening positive development. Such challenges may include emerging mental health issues and struggles with behavioral regulation. These interventions may be particularly critical during childhood when conduct-related challenges commonly emerge with associated impairments in key areas of functioning at school, home and in the community.
Keywords: mental health; childhood development; intervention; evidence-based interventions; family outcomes; disruptive behavior disorders; behavioral regulations; poverty; parenting; clinic implementation; stressors; communication; parent-child relationship